2007
DOI: 10.1248/cpb.55.1240
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids and Flavonoids from the Aerial Parts of Tithonia diversifolia and Their Cytotoxic Activity

Abstract: Tithonia diversifolia (HEMSL.) A. GRAY (Compositae) is native to Mexico and also grows in parts of Africa, Australia, Asia, and other countries of North America, and is commonly called Mexican sunflower or tree marigold.1) An extract of T. diversifolia has been traditionally used for the treatment of diabetes, diarrhea, menstrual pain, malaria, hematomas, hepatitis, hepatomas, and wound healing. 2-5)Pharmacological studies of Tithonia diversifolia showed that it has anti-diabetic, 6,7) anti-malarial, 8) anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 18 publications
2
35
0
4
Order By: Relevance
“…Depression in the blood profile after the adminis- tration of the plants extracts suggests that the plant extracts may have cytolytic or cytotoxic effects. It has documented that some of the components of the crude extracts have cytotoxic effects (Kuroda et al, 2007), but these may not include marrow stoma dysfunction or damage as seen with other known cytotoxic drugs like cytosine arabinoside (Ben-Ishay and Barak, 2001) since the rate of recovery of the red blood cell line was quicker.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression in the blood profile after the adminis- tration of the plants extracts suggests that the plant extracts may have cytolytic or cytotoxic effects. It has documented that some of the components of the crude extracts have cytotoxic effects (Kuroda et al, 2007), but these may not include marrow stoma dysfunction or damage as seen with other known cytotoxic drugs like cytosine arabinoside (Ben-Ishay and Barak, 2001) since the rate of recovery of the red blood cell line was quicker.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that isolated compounds showed cytotoxic activity against HL-60 leukemia cells (Kuroda et al, 2007). The cancer growth inhibitory property of the extract was further examined using a disease-oriented panel composed of 39 human cancer cell lines in the Japanese Foundation for Cancer Research by the same group.…”
Section: Resultsmentioning
confidence: 99%
“…T. diversifolia has been exhaustively studied 0378-8741/$ -see front matter © 2011 Elsevier Ireland Ltd. All rights reserved. doi:10.1016/j.jep.2011.04.067 and possesses several biological activities including the following: anti-inflammatory, analgesic, antimalarial, antiviral, antidiabetic, antidiarrhoeal and antimicrobial, among others (Cos et al, 2002;Owoyele et al, 2004;Kuroda et al, 2007). Besides these numerous, documented biological activities, this plant is important due to its substantial use within traditional medicine in several countries (Frei et al, 1998;Heinrich et al, 1998;Játem-Lásser et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found while using peripheral blood mononuclear cells, where 1 and 2 also presented cytotoxic effects, thus indicating nonselective toxicity. It has previously been shown that 1 has cytotoxic activity against HL-60 cells [19], but its activity has not yet been compared with that of the derivative 2. In the same work, compound 1b was isolated from T. diversifolia as a natural compound and was found to be approximately 10 times more active than 1.…”
Section: Resultsmentioning
confidence: 99%
“…Gray, Asteraceae) [2]. It shows cytotoxic [19], anti-inflammatory [33], and antifeedant activities [2], and thus is a promising compound for further research into its mechanisms of action in different targets. T. diversifolia, the source of 1, is used in folk medicine in many countries [8,14] and has anti-inflammatory and antimalarial properties [8].…”
Section: Introductionmentioning
confidence: 99%